Wall-Like Reinforced Concrete Columns Externally Confined by Means of Glass FRP Laminates. Issue 4 (April 2013) - De Luca, A.; Nardone, F.; Lignola, G. P.; Prota, A.; Nanni, A.
This paper discusses the laboratory testing of wall-like reinforced concrete (RC) columns externally confined with glass fiber reinforced polymer (GFRP) laminates and subjected to pure axial load. Specimens were characterized by an overall length of 3.05 m (10 ft), cross-sectional dimensions of 356 by 1, 041 mm (14 by 41 in). Three specimens were tested: one was unstrengthened (benchmark) and two were confined with GFRP laminates. Two different confining reinforcement ratios were considered. The experimental investigation aimed at characterizing: the confinement contribution in terms of axial strength and prevention of instability of longitudinal bars, and the sensitivity of any enhancement in performance to the confining reinforcement ratio. The experimental axial stress – axial strain curves are also discussed.